Low‐grade fibromyxoid sarcoma arising from the lung: A case report. Issue 18 (10th August 2021) - Yoshimura, Ryuichi; Nishiya, Masao; Yanagawa, Naoki; Deguchi, Hiroyuki; Tomoyasu, Makoto; Kudo, Satoshi; Shigeeda, Wataru; Kaneko, Yuka; Kanno, Hironaga; Sugai, Mayu; Shikanai, Shunsuke; Sugai, Tamotsu; et al.
Abstract: Low‐grade fibromyxoid sarcoma (LGFMS) is a rare sarcoma subtype that most commonly arises in young adults. This tumor typically presents in the deep soft tissues of the proximal extremities or trunk as a painless mass. Although the most common site of LGFMS metastasis is the lung, it is rarely the primary site. Here, we report a case of primary pulmonary LGFMS. A 22‐year‐old asymptomatic man was referred to our hospital for investigation of a lung mass that had been discovered incidentally. Computed tomography (CT) showed a well‐defined mass 4.0 cm in diameter in the upper lobe of the right lung. Malignancy was suggested by focal uptake of 18F‐fluorodeoxyglucose positron‐emission tomography (18‐FDG‐PET). Following surgery, postoperative histological analysis of the resected specimen demonstrated LGFMS based on histological and immunohistological findings. In particular, mucin 4 showed diffuse positivity in the spindle‐shaped tumor cells. In conclusion, LGFMS can arise in the lungs, and physicians should consider this entity as a differential diagnosis for solitary lung mass in young adults. Abstract : We herein report a rare case of primary pulmonary low‐grade fibromyxoid sarcoma. LGFMS could be considered a differential diagnosis of solitary lung mass in young adults. While definitive diagnosis for LGFMS is challenging, MUC4 is useful for definitive diagnosis in patients with FUS wild type.